Tenofovir-Based Antiretroviral Therapy in HBV–HIV Coinfection: Results from the TREAT Asia HIV Observational Database. Issue 1 (January 2016) - Boettiger, David C; Kerr, Stephen; Ditangco, Rossana; Chaiwarith, Romanee; Li, Patrick CK; Merati, Tuti Parwati; Pham, Thuy Thi Thanh; Kiertiburanakul, Sasisopin; Kumarasamy, Nagalingeswaran; Vonthanak, Saphonn; Lee, Christopher KC; Kinh, Nguyen Van; et al.
Background: The World Health Organization recommends HBV–HIV-coinfected individuals start antiretroviral therapy containing tenofovir. Here we describe first-line tenofovir use and treatment outcomes in coinfected patients in Asia. Methods: HBV surface antigen positive patients enrolled in the TREAT Asia HIV Observational Database who started first-line antiretroviral therapy were included. Logistic regression adjusted for period of treatment initiation was used to determine factors associated with tenofovir use. Generalized estimating equations were used to evaluate factors associated with alanine transaminase levels and CD4 + T-cell count on treatment. Results: There were 548 eligible patients, of whom 149 (27.2%) started tenofovir. Patients treated in high/high-middle income countries (odds ratio 4.4 versus low/low-middle, 95% CI 2.6, 7.4; P <0.001) and those with elevated baseline alanine transaminase (odds ratio 4.2 versus normal, 95% CI 2.4, 7.2; P <0.001) were more likely to receive tenofovir. Hepatitis C antibody positive patients (odds ratio 0.4 versus negative, 95% CI 0.2, 0.8; P =0.008) were less likely. In those starting antiretroviral therapy with elevated alanine transaminase, mean reduction after tenofovir initiation was 11.2 IU/l (95% CI 0.9, 21.6; P =0.034) lower compared with those using a non-tenofovir-based regimen although this did not significantly increase the chance of alanine transaminase normalization. Tenofovir use was not associated with a superior CD4 + T-cell response. Conclusions: HBV–HIV-coinfected patients in Asia are most likely to receive tenofovir if they are treated in a high/high-middle income country, have elevated alanine transaminase levels and are hepatitis C antibody negative. Compared to other antiretroviral therapies, tenofovir-based regimens more effectively reduce liver inflammation in HBV–HIV-coinfection but do not result in superior CD4 + T-cell recovery.